A Review on the Role of Small Nucleolar RNA Host Gene 6 Long Non-coding RNAs in the Carcinogenic Processes - Ghafouri-Fard, Soudeh; Khoshbakht, Tayyebeh; Taheri, Mohammad; Shojaei, Seyedpouzhia (Frontiers in Cell and Developmental Biology, 2021)
Being located on 17q25.1, small nucleolar RNA host gene 6 (SNHG16) is a member of SNHG family of long non-coding RNAs (lncRNA) with 4 exons and 13 splice variants. This lncRNA serves as a sponge for a variety of miRNAs, namely miR-520a-3p, miR-4500, miR-146a miR-16–5p, miR-98, let-7a-5p, hsa-miR-93, miR‐17‐5p, miR-186, miR-302a-3p, miR‐605‐3p, miR-140-5p, miR-195, let‐7b‐5p, miR-16, miR-340, miR-1301, miR-205, miR-488, miR-1285-3p, miR-146a-5p and miR-124-3p. This lncRNA can affect activity of TGF-β1/SMAD5, mTOR, NF‐κB, Wnt, RAS/RAF/MEK/ERK and PI3K/AKT pathways. Almost all studies have reported oncogenic effect of SNHG16 in diverse cell types. Here, we explain the results of studies about the oncogenic role of SNHG16 according to three distinct sets of evidence, i.e. in vitro, animal and clinical evidence.